Purification of HCC-specific extracellular vesicles on nanosubstrates for early HCC detection by digital scoring - Na Sun (Nature Portfolio, 2020)
Extracellular vesicles (EVs) are present in circulation at relatively early stages of disease, providing potential opportunities for early cancer diagnosis. Here, the authors report a covalent chemistry-based hepatocellular carcinoma (HCC)-specific EV purification system for early detection of HCC by performing digital scoring on the purified EVs.